PERAN KEPALA DESA DALAM MEREALISASIKAN PENGGUNAAN ANGGARAN DANA DESA DI DESA SELLI KECAMATAN BENGO KABUPATEN BONE - Neneng Hafsah (Jurnal Ilmu Akuntansi, 2021)
This study aims to determine the role of the Village Head of Selli in realize the village fund budget both in allocating the use of village funds and in planning, supervision and evaluating village funds. In this study, the data analysis used was descriptive qualitative analysis using three forms of data collection, namely; 1). Observation Technique, 2). Interview Techniques, and 3). Documentation Techniques. Research conducted in Selli Village, namely the Village Head has carried out his role in realizing the use of village funds through development, empowerment and community coaching, even though it hasn't run optimally. The results of the research that has been conducted in Selli Village, Bengo District, Bone Regency show that the Village Head of Selli has carried out his role in realizing the use of village funds starting from planning, allocation, and realizing.